Factors associated with knowledge and practice regarding oxygen administration: A cross-sectional study among registered nurses working in wards and ICUs at Muhimbili National Hospital in Dar es Salaam, Tanzania - Magdalena S. Kimario; Joel Seme Ambikile; Masunga K. Iseselo (PLoS ONE, 2025)
Background Oxygen is a vital therapy approved by WHO, crucial for critically ill patients as a supplemental treatment. Nurses’ pivotal role in oxygen administration is poorly understood. This study aimed to assess factors associated with oxygen administration to critically ill patients among nurses at Muhimbili National Hospital (MNH) in Dar es Salaam, Tanzania. Methods A descriptive cross-sectional study was conducted among 208 nurses using a simple random technique to recruit respondents. Data were collected in May 2022 via a self-administered questionnaire, designed and tested by the authors. Mean knowledge and practice scores were used to categorize knowledge and practice as high or low respectively. The Chi-square test and multiple logistic regression analyses were performed to evaluate factors associated with knowledge and practice regarding oxygen administration. Statistical significance was determined at a p-value less than 0.05. Results Of the 208 respondents, 96(46.2%) and 78(37.5%) had low knowledge and low practices regarding oxygen administration, respectively. Receiving in-service training on oxygen administration (AOR: 3.515; p<0.001) was positively associated with knowledge of oxygen administration. None of the factors showed a statistically significant association with the practice of oxygen administration. Conclusion A substantial proportion of nurses had inadequate knowledge and practices regarding oxygen administration. While none of the assessed factors were found to have a statistical association with practice on oxygen administration, it is important to note their clinical significance. Healthcare institutions can benefit from implementing regular in-service training programs to address these knowledge and skills gaps and ensure that nurses are well-prepared for proper oxygen administration. Additionally, ongoing monitoring and support are essential to help translate improved knowledge into effective clinical practices.